Penanganan Tindak Pidana Kekerasan Dalam Rumah Tangga Melalui Pendekatan Restorative Justice - Latumaerissa, Denny; Sopacua, Margie Gladis; Saimima, Judy Marria; Patty, Jetty (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: Domestic violence is a legal event that we often encounter in a society in Indonesia..The solution to family violence or the scope of a household when it is completed criminal law lines is not appropriate., Remembers that the perpetrator and the victim had a very close relationship., So it takes different ways of dealing with conflicts in that household.Purposes of Devotion: His dedication activities aimed at recognizing domestic violence, forms of domestic violence, the restorative justice, handling domestic rigidity through a restorative justice approach to forming a comprehension and legal awareness for the participant. Method of Devotion: Experience in the implementation of community law in halong, the city of ambon, through a discussion in panels which speakers for given the lectures was continued by question and answer session between spekers and participants.Results of the Devotion: The settlement of domestic violence by using conventional criminal justice in the fact that empiricals raise new issues of divorce..So to avoid the point., A more effective cdrt settlement model is needed without causing any damage to the household's wholeness.Restorative justice is an alternative or some other way of criminal justice by putting a priority on the integration of the perpetrators and the victims or the community as one unit to find solutions and go back to a good link between the perpetrators..Counseling activities are preceded by pretesting, Then continue the legal counseling activity in the public hall over a panel-based discussion where the authoritarian delivers the material in turns and then proceeds with the question-responsibility between the cooker and the community. Then do a post-tes.